Análise do comportamento e planejamento cultural: utopia ou distopia? - Rocha, César Antonio Alves da (2018)
The notion of science has undergone continuous transformations throughout history, from the Aristotelian conception of contemplative knowledge to the modern ideal of operative knowledge. The modern perspective on science as knowledge was received with antagonistic expectations in the philosophical sphere. On one hand, what is identified as a Promethean narrative highlights the potentiality of science as a means for the emancipation of humanity and the catalyzing of human progress; on the other, the Faustian narrative represents opposing expectations, alerting to the hazards involved in the employment of science and its by-products to the domain of the natural world. Taken to the extreme, these two tendencies symbolize what, in the literary context, can be identified as the established antithesis between utopia and dystopia. In principle applicable to science in general, this oppositional duality is paralleled in the manner in which the ideas of B. F. Skinner, theoretician of behavioral analysis and proponent of the notion of cultural design, were received. Seen with enthusiasm by some and suspicion by others, Skinner's ideas about the science of behavior in general and the management of life in society in particular have been the subject of controversies still unresolved today. This work aimed at a detailed examination of the affinities of the Skinnerian proposition of cultural planning with the notions of utopia and dystopia, with special attention to possible relations with the second notion, in order to answer the question presented in the title: would cultural design implie utopia or dystopia? As an analytical strategy, the Prometheus-Faustian duality was used as a key to read and examine the Skinnerian text, chapter by chapter, in search of inclinations for each of these tendencies. The path pursuited initially involved an analysis of the Skinnerian view on science, technology and behavioral control; then the target was the theoretical formulation of cultural design; later, it was investigated how the proposition was illustrated by the author in its fictional work, Walden Two; finally, starting from a panorama on the genesis and development of the notions of utopia and dystopia, affinities were probed between the proposal of cultural design and these two notions. The results reveal that it is possible to identify inclinations both to the notion of utopia and to the notion of dystopia, and that the complexity of Skinnerian thought prevents an unequivocal answer to the title question. This result led to a conclusion that proposes a re-reading about the proposal of cultural design that relativizes and conceives it outside the dyad utopia-dystopia. The thesis advanced in this work proposes a parsimonious perspective, which updates the proposition of cultural design in light of contextualist and pluralistic objections, preserving its most auspicious factors, such as the experimentalist attitude, and abandoning its anachronistic traits, such as the technocratic platform. Thus, the proposal of cultural design is conceived as a gradualist effort to test contingency arrangements alternative to those institutional arrangements then in development, focusing on small-scale reforms that prioritize, as far as possible, the controlo of people by people, not as means for radical transformations or the establishment of utopian scenarios.